2018
DOI: 10.1111/josh.12648
|View full text |Cite
|
Sign up to set email alerts
|

Examining Time to Treatment and the Role of School‐Based Health Centers in a School‐Based Sexually Transmitted Infection Program

Abstract: For students testing positive in the Chicago school-based STI program, time to treatment is accelerated in locations with SBHCs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 17 publications
0
15
0
Order By: Relevance
“…Schools have been a venue for the delivery of complex sexual and reproductive health interventions such as sex education initiatives [26] and risk behavior reduction programs [27]. School-based STI screening initiatives can offer opportunities for diagnosis and treatment of STIs among adolescents who may not be able to access sexual health services elsewhere, and therefore reduce time to treatment [14]. A previous study which examined screening in New Orleans high schools during the 1997-1998 school year indicated that the program could be cost-effective and cost-saving [28].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Schools have been a venue for the delivery of complex sexual and reproductive health interventions such as sex education initiatives [26] and risk behavior reduction programs [27]. School-based STI screening initiatives can offer opportunities for diagnosis and treatment of STIs among adolescents who may not be able to access sexual health services elsewhere, and therefore reduce time to treatment [14]. A previous study which examined screening in New Orleans high schools during the 1997-1998 school year indicated that the program could be cost-effective and cost-saving [28].…”
Section: Discussionmentioning
confidence: 99%
“…Sustaining school-based screening requires considerable resources at the local level [9,14]. All screening efforts require funding, infrastructure, and human resources.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The American Academy of Pediatrics (AAP) recommends at least one preventive health visit per year. The data, however, show that only 40-80% of adolescents report a primary care visit within 12 months [9][10][11]. A 2010 study of insured adolescents, revealed that one-third had no preventive care visits between the ages of 13 through 17 years, and another 40% had only one preventive care visit during this 4 year period of their lives [12].…”
Section: Utilization Of Health Care By Adolescentsmentioning
confidence: 99%